The Numerical Solution for Solving nth Order Integro-Differential Equations via Boubaker Scaling Functions - Ouda, Eman Hassan (Al-Qadisiyah Journal of Pure Science, 2022)
In this paper, the continuous Boubaker scaling functions were constructed with the presentation on the interval [0,1], which obtained depending on Boubaker polynomials. In this current study the Boubaker scaling polynomial has been applied for solving the nth order integro–differential equations (IDE’s). The collocation method with the aid of Boubaker scaling functions together were utilized to transform the higher order integro–differential equations into a problem of linear system algebraic equations. Some numerical examples were added to show the simplicity and accuracy of the proposed technique. The results have been compared with the exact solution using Matlab and illustrated by graphs.